Africa must be modern : a manifesto - Taiwo, Olufemi, 1956- (Indiana University Press, 2014)
In a forthright and uncompromising manner, Olúfémi Táíwò explores Africa's hostility toward modernity and how that hostility has impeded economic development and social and political transformation. What has to change for Africa to be able to respond to the challenges of modernity and globalization? Táíwò insists that Africa can renew itself only by fully engaging with democracy and capitalism and by mining its untapped intellectual resources. While many may not agree with Táíwò's positions, they will be unable to ignore what he says. This is a bold exhortation for Africa to come into the 2.